2015
DOI: 10.3390/agriculture5030427
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence and Toxicity of Indospicine to Grazing Animals

Abstract: Indospicine is a non-proteinogenic amino acid which occurs in Indigofera species with widespread prevalence in grazing pastures across tropical Africa, Asia, Australia, and the Americas. It accumulates in the tissues of grazing livestock after ingestion of Indigofera. It is a competitive inhibitor of arginase and causes both liver degeneration and abortion. Indospicine hepatoxicity occurs universally across animal species but the degree varies considerably between species, with dogs being particularly sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 40 publications
0
39
0
2
Order By: Relevance
“…1) is an unusual amino acid which occurs only in members of the Indigofera genus with about 700 species of this genus distributed across tropical Africa, Asia, Australia and North and South America. 2 The toxicological symptoms were found to be identical to those found in rats orally dosed with indospicine 3 and it was concluded that indospicine in Indigofera spp. that contain this non-proteogenic amino acid and also in secondary (carnivore) consumers of meat from these herbivores.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…1) is an unusual amino acid which occurs only in members of the Indigofera genus with about 700 species of this genus distributed across tropical Africa, Asia, Australia and North and South America. 2 The toxicological symptoms were found to be identical to those found in rats orally dosed with indospicine 3 and it was concluded that indospicine in Indigofera spp. that contain this non-proteogenic amino acid and also in secondary (carnivore) consumers of meat from these herbivores.…”
mentioning
confidence: 70%
“…2 The toxicological symptoms were found to be identical to those found in rats orally dosed with indospicine 3 and it was concluded that indospicine in Indigofera spp. 1,10 Indospicine is structurally analogous to arginine (2), possessing an amidine function rather than a guanidine, and as an arginine antagonist competes with arginine for the active site of arginase and competitively blocks incorporation of arginine into protein with consequential inhibition of protein and DNA synthesis. Although this amino acid is commonly associated with liver toxicity, the embryotoxicity and teratogenicity of indospicine, 4 as well as its ability to inhibit nitric oxide synthase 5 have also been examined.…”
mentioning
confidence: 70%
“…"Toxicity -lab animal" described 184 species reported as toxic in studies in which small animals in confinement were overfed 185 quantities of a plant or plant extract, since results of such studies are not always relevant to 186 normal exposure. "Toxicity -predicted" was used to flag species without reports of illness, but 7 that had been reported in survey studies to contain chemicals similar to other toxic species (in 188 particular, Davis, 1982;Williams & GĂłmez-Sosa, 1986;Wink, Meisner, & Witte, 1995;189 Fletcher, Al Jassim, & Cawdell- Smith, 2015). Generally, we observed that species whose 190 chemistry and bioactivity are understudied should similarly be suspected of toxicity when 191 toxicity is common within the same genus.…”
Section: Establishment Of Papgi Interface Legume Data Extracted Frommentioning
confidence: 94%
“…“Toxicity—lab animal” described species reported as toxic in studies in which small animals in confinement were overfed quantities of a plant or plant extract, since results of such studies are not always relevant to normal exposure. “Toxicity—predicted” was used to flag species without reports of illness, but that had been reported in survey studies to contain chemicals similar to other toxic species (in particular, Davis, ; Fletcher, Al Jassim, & Cawdell‐Smith, ; Williams & GĂłmez‐Sosa, ; Wink, Meisner, & Witte, ). Generally, we observed that species whose chemistry and bioactivity are understudied should similarly be suspected of toxicity when toxicity is common within the same genus.…”
Section: Methodsmentioning
confidence: 99%
“…"Toxicity-predicted" was used to flag species without reports of illness, but that had been reported in survey studies to contain chemicals similar to other toxic species (in particular, Davis, 1982;Fletcher, Al Jassim, & Cawdell-Smith, 2015;Williams & GĂłmez-Sosa, 1986;Wink, Meisner, & Witte, 1995). Generally, we observed that species whose chemistry and bioactivity are understudied should similarly be suspected of toxicity when toxicity is common within the same genus.…”
Section: Toxicological Data Integration Within Papgimentioning
confidence: 97%